2022
DOI: 10.1007/s00441-022-03636-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteomics reveals diverse stimuli activate distinct signaling pathways during neutrophil activation

Abstract: Neutrophils display functional heterogeneity upon responding diversely to physiological and pathological stimulations. During type 2 diabetes (T2D), hyperglycemia constitutively activates neutrophils, leading to reduced response to infections and on the other hand, elevated metabolic intermediates such as homocysteine induce bidirectional activation of platelets and neutrophils leading to thrombosis. Hence, in the context of T2D-associated complications, we examined the influence of high glucose, homocysteine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…This observation is supported by various animal studies indicating that obesity predisposes neutrophils to spontaneously release weak NETs without stimulation (Cichon et al 2021, Burczyk et al 2022. This process is thought to involve C-Jun-N-terminal kinase (JNK) induced Rho GTPase kinase activity which is known to play an important role in NADPH oxidase activation as well as regulation of actin cytoskeletal rearrangement, both of which are required for NETs formation (Lacy & Eitzen 2008, Gavillet et al 2018, Thimmappa et al 2022. The externalized components of NETs which include chromatin, citrullinated histones, cell-free DNA, nucleosomes, and NE persist in vasculature and have been linked to the pathogenesis of disease progression (Kaplan & Radic 2012, Papayannopoulos 2018).…”
Section: Box 1 Terminologymentioning
confidence: 76%
See 2 more Smart Citations
“…This observation is supported by various animal studies indicating that obesity predisposes neutrophils to spontaneously release weak NETs without stimulation (Cichon et al 2021, Burczyk et al 2022. This process is thought to involve C-Jun-N-terminal kinase (JNK) induced Rho GTPase kinase activity which is known to play an important role in NADPH oxidase activation as well as regulation of actin cytoskeletal rearrangement, both of which are required for NETs formation (Lacy & Eitzen 2008, Gavillet et al 2018, Thimmappa et al 2022. The externalized components of NETs which include chromatin, citrullinated histones, cell-free DNA, nucleosomes, and NE persist in vasculature and have been linked to the pathogenesis of disease progression (Kaplan & Radic 2012, Papayannopoulos 2018).…”
Section: Box 1 Terminologymentioning
confidence: 76%
“…Defects in intracellular glucose cycling can therefore negatively impact key neutrophil functions, whereas a disproportionate increase in glycolysis due to the excessive availability of extracellular glucose fuels persistent neutrophil activity (Sadiku et al 2021). Thimmappa et al (2022) elucidated specific neutrophil responses following various activating signals by assessing the differential phosphorylation of proteins using an unbiased quantitative phosphoproteomics approach. The authors indicated that the ex vivo exposure of neutrophils to hyperglycaemia for a period of 3 h induced a 6-fold increase in NETs formation compared to only a 3-fold increase upon stimulation with either lipopolysaccharide (LPS) (bacterial infection) or the metabolic intermediate homocysteine for the same period.…”
Section: Box 1 Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that hyperglycemia increases the number of circulating neutrophils ( 103 ). However, the later studies found that the function of neutrophils is impaired in high glucose conditions, and their phagocytic and killing functions are inhibited to a certain extent ( 104 , 105 ). These results reflected that hyperglycemia induces massively impaired neutrophils in peripheral blood, resulting in chronic inflammation.…”
Section: Diabetic Osteoporosismentioning
confidence: 99%
“…Accordingly, cell surface markers such as olfactomedin, CD177, CXCR4 + CD62L − and many others have also been basis of defining neutrophil subtypes which showed functional alterations in diseases [ 29 31 ]. Moreover, studies from many laboratories, including ours, have shown activation of stimulus-specific signalling pathways in neutrophils [ 32 , 33 ]. For example, high glucose, LPS and homocysteine representing stimuli for diabetes, infections and thrombosis, respectively, induced distinct set of kinases which were associated with specific functions of neutrophils [ 33 ].…”
Section: Introductionmentioning
confidence: 99%